Minor extended-spectrum β-lactamases. Issue 11 (November 2010) - Akinci, Esragul; Vahaboglu, Haluk
Over the last few decades, various extended-spectrum β-lactamases (ESBLs), which are remotely related to the classical TEM and SHV families, have emerged. Among these, CTX-M, VEB and PER variants are of particular interest due to their widespread dissemination. This article will focus on these emerging ESBLs. CTX-M was first identified from an Escherichia coli strain in Germany and since then, a rapidly growing family of ESBLs has formed worldwide. There are now more than 90 CTX-M variants. VEB-1 ESBL is widespread in Southeast Asia. It was first identified in an E. coli strain isolated from a Vietnamese boy in 1996. After the initial discovery, it spread to other species. PER-1, now reported from various continents, was restricted to Turkish hospitals for years after the first identification in a strain of Pseudomonas aeruginosa in 1993. The worldwide dissemination of ESBLs is a healthcare crisis that deserves special attention.